Monografia. Estudio Del Arpeo Equino Y Su Manejo Quirurgico (2024)
Equine stringhalt or bunny hop is a neuromuscular pathology that affects horses, characterized by an exaggerated and involuntary contraction of the flexor muscles of the tarsus, which causes an abnormal movement of the hind limb, which can be in one or both limbs, especially during the lifting phase of the limb when walking.